2019
DOI: 10.5964/jnc.v5i1.177
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of non-symbolic number processing in children with mathematical learning disability

Abstract: The functional origin of Mathematical Learning Disability (MLD), an impairment affecting mathematics learning, remains controversial. We aimed to study the number sense deficit hypothesis in children with MLD. We explored the processing of non-symbolic numbers in Quebec French-speaking 8-9-year-old children with three non-symbolic tasks (number comparison, number matching and dot set selection task). Results showed that children with MLD were as successful as typically developing children in a comparison task,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…However, the VLA group exhibited significant deficits in subitizing compared to the controls and the LA group. Previous studies have shown similar results in children with mathematical learning disabilities (Lafay et al, 2019;Schleifer & Landerl, 2011). Also, we found significant differences between TA and the two groups with arithmetical difficulties in the counting range.…”
Section: Contribution Of Exact Numerosity Estimation and Numerical Mapping Skills To Arithmetic Achievementsupporting
confidence: 86%
“…However, the VLA group exhibited significant deficits in subitizing compared to the controls and the LA group. Previous studies have shown similar results in children with mathematical learning disabilities (Lafay et al, 2019;Schleifer & Landerl, 2011). Also, we found significant differences between TA and the two groups with arithmetical difficulties in the counting range.…”
Section: Contribution Of Exact Numerosity Estimation and Numerical Mapping Skills To Arithmetic Achievementsupporting
confidence: 86%
“…Other studies, however, have not found such effects (e.g. De Smedt & Gilmore, 2011;Lafay et al, 2019). In contrast, more consistent and robust differences between children with or without MLD or dyscalculia (Cañizares et al, 2012;De Smedt et al, 2013;De Smedt & Gilmore, 2011;Desoete et al, 2012;Landerl et al, 2009) have been found in studies using SNMP measures, thus supporting "access deficit" (Rousselle & Noël, 2007) as an alternative explanation for dyscalculia, according to which the core deficit lies in not being able to access the number magnitude in symbols.…”
Section: Snmp and Wm As Predictors Of Mathematical Learning Difficultiesmentioning
confidence: 90%
“…Some studies using non-symbolic NMP measures have shown children with dyscalculia to perform poorly in tasks of comparing two magnitudes (Desoete et al, 2012;Landerl et al, 2009;Mazzocco et al, 2011), or matching them (i.e. deciding whether two magnitudes are same or not) (Lafay et al, 2019), thus supporting the "defective number module" (Butterworth, 2005) as a primary cause of dyscalculia. Other studies, however, have not found such effects (e.g.…”
Section: Snmp and Wm As Predictors Of Mathematical Learning Difficultiesmentioning
confidence: 99%
“…Mathematical learning difficulties have an important prevalence, ranging from 1 to 10% depending on the research conditions (Chinn, 2014;De La Peña & Bernabéu, 2018;Lafay et al, 2019). These mathematical difficulties negatively influence classroom learning environment and daily life activities (Aguilar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%